Les mecanismes de la confiance en traduction - aspects relationnels - Froeliger, Nicolas (The Journal of Specialised Translation, 2004)
This paper attempts to make sense of various confidence-related behaviors that, together, form a prerequisite to producing valid translations. Self-confidence, first, is a precondition to avoiding word-for-word translation, exaggerated faith in the author and the temptation to blur everything out. Then, in order to establish trust in the relation to others, the translating sector tends to imitate the workings of initiatory societies. This leads to two paradoxes. First, confidence and trust are necessarily implicit, leaving translators unprotected against those that betray their confidence. Second, those workings breed a tendency toward closure, in absolute contradiction with the very nature of translation. This pattern may be an inheritance from earlier historical stages. It is associated with a dialectics of discretion: a translator is supposed to be invisible, but cannot produce valid texts without having his role duly recognized. Thus, the main point of relational mechanisms governing confidence in translation is that of authority: who decides? If this responsibility is really shared, one can start translating. A later paper will deal with the textual aspects of confidence.